The diversity of the genus Aricidea (Polychaeta: Paraonidae) from the Sea of Marmara, with descriptions of two new species and two new records for the Mediterranean fauna - Erdoğan-Dereli, Deniz; Çinar, Melih Ertan (Zootaxa, 2020)
This paper reports 13 Aricidea species from the Sea of Marmara. The Aricidea specimens were collected at 98 stations in the region in 2012 and 2013 from soft and hard substrata at depths ranging from 0 to 1200 m. Among the material, two new species, namely Aricidea (Acmira) katzmanni n. sp. and Aricidea (Acmira) pseudoassimilis n. sp., and 11 known species were discovered. Aricidea mirunekoa and A. bulbosa are new records for the Mediterranean fauna; A. (Acmira) annae and A. (Aricidea) wassi are new records for the Sea of Marmara. Aricidea (Acmira) katzmanni n. sp. is characterized by having a long, digitiform antenna; no notopodial papillae on the posterior part of the branchial region; and hook shaped modified neurochaetae with a strong hood and fragile arista. Aricidea (Acmira) pseudoassimilis n. sp. is characterized by having a short, digitiform antenna; interramal lobes between notopodia and neuropodia; hook-shaped modified neurochaeta that gets subterminally thinner with a rounded tip. As A. (Strelzovia) bulbosa has been only previously reported from the Gulf of Suez (Red Sea), it could be a new alien species for the Sea of Marmara and Mediterranean Sea. Based on the characters that have been overlooked so far, the subspecies A. suecica meridionalis and A. capensis bansei were raised to species level, A. meridionalis n. stat. and A. bansei n. stat. The present paper reports the usage of ciliary bands and slits on the prostomium and body, swellings/ridges in the branchial region, and the shape and distribution of sense organs in the taxonomy of Aricidea. All species were described and figured.